Problematika Penggunaan AI dalam Pencarian Hukum Islam pada Pembelajaran Fikih di STAI Al Washliyah Barabai - Gt. Aiman Rozan; Muhammad Hendry; Nuthpaturrahman (PT. Hasba Edukasi Mandiri, 2026)
This research is motivated by the increasing use of Artificial Intelligence (AI) in Islamic jurisprudence (fiqh) learning at STAI Al Washliyah Barabai. AI is used by students to quickly search for evidence, understand material, and obtain Islamic legal information. However, the use of AI also raises various problems, such as a lack of verification of legal sources, dependence on instant answers, and low critical thinking skills. This study used field research with a descriptive qualitative approach. The research subjects consisted of lecturers and students of the Islamic Religious Education Study Program at STAI Al Washliyah Barabai. Data were collected through observation, interviews, and documentation, then analyzed through the stages of editing, classification, and interpretation. Data validity was tested using source triangulation and technical triangulation. The results show that AI provides benefits in helping students understand Islamic jurisprudence material, obtain Islamic legal information, and simplify difficult-to-understand concepts. However, the use of AI also raises several problems, namely low verification of legal sources, the emergence of dependence on AI, and differences between AI answers and lecturers' explanations and Islamic jurisprudence references.